Moving Working Families Forward Third Way Policies That Can Work - Cherry, Robert (New York University Press, 2011)
"Cherry and Lerman have written a compelling book that challenges the orthodoxies of both the political ‘left’ and ‘right’, and that promotes a set of policies to improve the economic status of lower-to-middle income working families. All who care about the well-being of working families will learn a great deal from their analysis."—Harry Holzer, Professor of Public Policy, Georgetown University "Offers highly sophisticated proposals for helping working families advance in the wake of welfare reform. Cherry and Lerman are very expert, and they write very well."—Lawrence M. Mead, Professor of Politics and Public Policy, New York University Even as our political system remains deeply divided between right and left, there is a clear yearning for a more moderate third way that navigates an intermediate position to address the most pressing issues facing the United States today. Moving Working Families Forward points to a Third Way between liberals and conservatives, combining a commitment to government expenditures that enhance the incomes of working families while recognizing that concerns for program effectiveness, individual responsibility, and underutilization of market incentives are justified. Robert Cherry and Robert Lerman provide the context to understand the distinctive qualities of Third Way policies, focusing on seven areas that substantially affect working families: immigration, race and gender earnings disparities, education, housing, strengthening partnerships, and federal taxes. Balancing empirical studies with voices of working class people, they offer an important perspective on how public policies should be changed. A timely approach, Moving Working Families Forward makes policy recommendations that are both practical and transformative